تاريخ تصنيف المعاجم العربية - Fathi Hidayah (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2018)
The development of the learning Arabic language cannot be separated from the development Arabic dictionary. As one of the tools to understand Arabic, Arabic dictionary has been compiled into many languages. As part of that must be owned by the Arab language learners, the development of the preparation of the Arabic dictionary does much review. In Indonesia, there are famous names as Arab-Indonesia dictionary. Search of the history of the compilation a dictionary of Arabic being the one thing that is very important to know the complexities of the world of lexicography both in the Arab world as well as in the non-Arab countries, especially in Indonesia.